Consortium Blockchain Framework for Secure Digital Medical Record Innovation - Sembiring, Irwan; Aji, Bintang Kristianto; Bayu, Teguh Indra (Pandawan, 2026)
Healthcare systems face growing challenges in protecting patient information, with more than 276 million healthcare records breached in 2024 alone. This study presents a proof-of-concept consortium blockchain framework that integrates Near Field Communication (NFC) based authentication with smart contract driven consensus to securely verify and synchronize Electronic Medical Records (EMRs) across multiple healthcare facilities. The system was tested in a simulated network of three Virtual Private Servers, achieving an average NFC verification time of 2.9 seconds and a consensus propagation time of 0.4 seconds, demonstrating stable performance suitable for near-real-time operations.Although these results are promising, the evaluation was limited to synthetic datasets, small-scale network conditions,and basic database security configurations. Future work will focus on scaling the system to larger and more diverse networks, strengthening cybersecurity measures, and ensuring full compliance with HIPAA and GDPR standards. By supporting the United Nations’3rd Sustainable Development Goal on Health and the 9th Sustainable Development Goal on Infrastructure and Innovation, this research contributes to the development of secure, interoperable, and sustainable healthcare information systems.